Eksistensi Sastra Indonesia Dalam Konteks Globalisasi Dan Modernitas - Alifia Sastia Febriana Resky (CV. SINAR HOWUHOWU, 2025)
This research examines the existence of Indonesian literature amidst the transformative currents of globalization and modernity. This phenomenon presents dual challenges in the form of global market hegemony, dominated by translated works, and a shift in literary culture driven by the advancement of digital technology. The purpose of this article is to critically analyze the challenges faced, the adaptation strategies developed by authors and literary industry stakeholders, and their implications for the position and form of contemporary Indonesian literature. Employing a qualitative approach with a descriptive-analytical design, this research utilizes library research on selected literary works from the 2005-2025 period and relevant secondary sources. The findings indicate that Indonesian literature faces significant pressure from market competition and the fragmentation of reader attention caused by digital media. However, authors are responding creatively through strategies of genre hybridization—blending local content with global formats—and leveraging digital platforms to build communities and market their work independently. The study concludes that the existence of Indonesian literature is not under threat, but is rather undergoing a transformation into a more hybrid, dynamic, and digitally integrated form, wherein its sustainability depends on the ability of its ecosystem to creatively negotiate between local and global forces.